POLITICAL PARTIES AND DEMOCRATIZATION OF SOCIETY (Scientific journal of the Fergana State University, 2023)
This article discusses the creation and improvement of the law about the principles of building and development of the democratic civil society in Uzbekistan and foundation of the role of political party in this process.